BTST thin film sensor application : heat indicator - Nur Faizah Jaafar
This paper is based on the design and analysis of heat indicator using Barium Tantalum Strontium Titanate (BTST) thin film sensor which was fabricated in Universiti Malaysia Perlis (UniMAP) Cleanroom by their researchers. This project was done to see the potential of the sensor itself.